Shadow politics: Freemasonry and Secret Societies in Spain during the Liberal Triennium (1820-1823) - Ceballos Coz, Sergio (2023)
The Liberal Triennium (1820-1823) is widely known for being the second constitutional regime in thehistory of Spain, inaugurated by the triumph of Riego’s pronouncement in 1820. In that sense, it ismarked by the enormous difficulties that the liberals faced in establishing an alternative state to theabsolutist one; a state in which king Ferdinand vii felt both deeply uncomfortable and restrained. Inthe same way, a long shadow still looms over this political regime, destined to fail after having becomea system controlled by the actions of mysterious clandestine societies, including Freemasonry.